2022
DOI: 10.1021/acsanm.1c04158
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Ti-Deficient Ti3C2 MXene Nanosheets as NH3 Gas Sensors

Abstract: Sensitive gas sensors are becoming increasingly important in toxic gas detection and environmental monitoring. The applications of conventional gas sensors are limited due to their low sensitivity or high operating temperature. MXenes with high conductivity are conducive to the rapid transmission of electrons and are suitable as highly sensitive NH3 gas sensors. Considering the limited research on the experimental details and sensing mechanism of MXene-based NH3 gas sensors, our research focuses on precisely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Li et al showed that Ti-deficient Ti 3 C 2 O 2 MXene has a relatively stronger physical interaction with NH 3 and is comparatively more suitable for a highly sensitive NH 3 gas sensor. 160 However, the studies above reported on the gas sensing behavior of MXenes with a single functional group as surface termination. The synthesized MXene materials have a combination of −F, −O, and −OH surface termination groups, with ratios hugely based on the etchant type and the synthesis route.…”
Section: ■ Mxene Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al showed that Ti-deficient Ti 3 C 2 O 2 MXene has a relatively stronger physical interaction with NH 3 and is comparatively more suitable for a highly sensitive NH 3 gas sensor. 160 However, the studies above reported on the gas sensing behavior of MXenes with a single functional group as surface termination. The synthesized MXene materials have a combination of −F, −O, and −OH surface termination groups, with ratios hugely based on the etchant type and the synthesis route.…”
Section: ■ Mxene Propertiesmentioning
confidence: 99%
“…N atoms of the NH 3 molecule located on the top of the Hf atom in a C-vacancy Hf 2 CO 2 (TH–CVH) were found to be helpful as a reusable gas sensor under strain conditions. Li et al showed that Ti-deficient Ti 3 C 2 O 2 MXene has a relatively stronger physical interaction with NH 3 and is comparatively more suitable for a highly sensitive NH 3 gas sensor . However, the studies above reported on the gas sensing behavior of MXenes with a single functional group as surface termination.…”
Section: Mxene-based Gas Sensorsmentioning
confidence: 99%
“…Most experimental sensors concentrate on the terminational groups over the MXene. In a recent theoretical calculation work, Li et al proposed the Ti vacancy may enhance the interaction of Ti-deficient Ti 3 C 2 O 2 with NH 3 molecule, [205] compared to pristine Ti 3 C 2 O 2 species. Indeed, the Ti-deficient MXene-based sensor demonstrates larger current change than the pristine MXene when exposed to NH 3 gas.…”
Section: Gas Sensors Based On Mxene Chemiresistorsmentioning
confidence: 99%
“…Ti 3 C 2 is a typical transition metal carbide with multilayer metal ion adsorption behavior, with ultra-high electrical conductivity and extraordinary mechanical and electronic properties [ 17 , 18 ]. Ti 3 C 2 is expected to be the most competitive material candidate in some fields, such as high-performance ultra-thin electronics and storage [ 19 , 20 ]. Mathis et al [ 21 ] investigated the MXene nanosheets (Al-Ti 3 C 2 ), and found they have higher quality, increased oxidation resistance, and electronic conductivity increased to 20,000 S/cm.…”
Section: Introductionmentioning
confidence: 99%